A systematic review of research on distance language teaching (2011–2020): Focus on methodology. (April 2022) - Vorobel, Oksana
Abstract: This article systematically reviews empirical studies on distance language teaching (DLT) focusing on their methodology. Thorough search for empirical studies published between 2011 and 2020 and screening of the articles based on the inclusion and exclusion criteria resulted in identifying 197 studies. The selected peer-reviewed publications were analyzed for their distribution over time and in different journals, their foci of investigation, and methodological design features, such as methodological approaches, contexts, language learners, target languages, and technologies. The findings are discussed in reference to other systematic reviews and critical reviews of research on distance language education, teaching languages at a distance, computer-assisted language learning (CALL) and second language learning, Web 2.0 tools, mobile language learning, online learning and teaching, and others. Finally, the review highlights the gaps in the current research and provides suggestions for future studies on DLT.